Parental Pedagogical Culture As An Individual Of The Family Institute - Khaydarova Xilola Rakhimberdievna (Zien Journals, 2021)
The article analyzes that the pedagogical culture of parents is an integral part of the family institution. Concepts such as pedagogical culture, virtual culture, etc., were also highlighted, and a new form of message delivery was discussed, despite the fact that the information structure of the Internet is close to that of the media. The means of recognition and presentation of family values, systematic psychological, pedagogical and socio-economic assistance to the family, promotion of traditional educational values, development and implementation of a multifaceted program for the development of parental pedagogical culture are studied separately in the proposed conditions
Keywords: Parent; culture; children; internet